Bone Impairment in a Large Cohort of Chinese Patients With Tumor‐Induced Osteomalacia Assessed by HR‐pQCT and TBS. (3rd January 2022) - Ni, Xiaolin; Feng, Yiming; Guan, Wenmin; Chi, Yue; Li, Xiang; Gong, Yiyi; Zhao, Nan; Pang, Qianqian; Yu, Wei; Wu, Huanwen; Huo, Li; Liu, Yong; et al.
ABSTRACT: Tumor‐induced osteomalacia (TIO) is a rare paraneoplastic syndrome caused by excessive production of fibroblast growth factor 23 (FGF23) by a tumor. Previous studies have revealed generalized mineralization defects and low areal bone mineral density (aBMD) in TIO. However, data on the bone microarchitecture in TIO are limited. In this study, we evaluated the microarchitecture in the peripheral (distal radius and tibia) and axial (lumbar spine) skeleton using high‐resolution peripheral quantitative computed tomography (HR‐pQCT) and trabecular bone score (TBS) and investigated related factors in a large cohort of Chinese patients with TIO. A total of 186 patients with TIO who had undergone dual‐energy X‐ray absorptiometry (DXA) or HR‐pQCT scans were enrolled. Compared with age‐, sex‐, and body mass index (BMI)‐matched healthy controls, TIO patients ( n = 113) had lower volumetric BMD, damaged microstructure, and reduced bone strength in the peripheral skeleton, especially at the tibia. The average TBS obtained from 173 patients was 1.15 ± 0.16. The proportion of patients with abnormal TBS (<1.35) was higher than that with low L1 to L4 aBMD Z ‐score ( Z ≤ −2) (43.9% versus 89.6%, p < 0.001). Higher intact fibroblast growth factor 23 (iFGF23), intact parathyroid hormone (iPTH), alkaline phosphatase, and β‐isomerized C‐terminal telopeptide of type I collagen (β‐CTx) levels, more severe mobility impairment, and a history of fracture were associated with poorer HR‐pQCT parameters but not with lower TBS. However, greater height loss and longer disease duration were correlated with worse HR‐pQCT parameters and TBS. Moreover, TBS was correlated with both trabecular and cortical HR‐pQCT parameters in TIO. In conclusion, we revealed impaired bone microarchitecture in the axial and peripheral skeleton in a large cohort of Chinese TIO patients. HR‐pQCT parameters and TBS showed promising advantages over aBMD for assessing bone impairment in patients with TIO. A longer follow‐up period is needed to observe changes in bone microarchitecture after tumor resection. © 2021 American Society for Bone and Mineral Research (ASBMR).